2006
DOI: 10.1002/ajmg.b.30303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of single nucleotide polymorphisms in genes in the chromosome 12Q24.31 region points to P2RX7 as a susceptibility gene to bipolar affective disorder

Abstract: Previous results from our genetic analyses using pedigrees from a French Canadian population suggested that the interval delimited by markers on chromosome 12, D12S86 and D12S378, was the most probable genomic region to contain a susceptibility gene for affective disorders. Association studies with microsatellite markers using a case/control sample from the same population (n = 427) revealed significant allelic associations between the bipolar phenotype and marker NBG6. Since this marker is located in intron 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
138
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(152 citation statements)
references
References 62 publications
10
138
4
Order By: Relevance
“…The 21 bp deletion in exon thirteen of P2RX7 15 was not observed in any of the bipolar disorder individuals. The data for six of the seven SNPs were in Hardy-Weinberg equilibrium (HWE) for the control samples.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The 21 bp deletion in exon thirteen of P2RX7 15 was not observed in any of the bipolar disorder individuals. The data for six of the seven SNPs were in Hardy-Weinberg equilibrium (HWE) for the control samples.…”
Section: Resultsmentioning
confidence: 78%
“…No correction for multiple testing has been applied because the appropriate method for correcting these analyses is not clear. Data for association between rs2230912 (P2RX7-E13A) and bipolar disorder was published in the first P2RX7 bipolar study 15 and also in a follow-up study on major depression. 16 The minor allele (G) in all three studies was found at an increased frequency in patients with mood disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another putative gain-of-function polymorphism described recently, the Q460R substitution, appears to enhance pore activity of the P2X 7 receptor [58]. Increasing evidence from genetic association studies have demonstrated that the polymorphisms of the P2X 7 gene are implicated in various diseases such as chronic lymphocytic leukemia, tuberculosis, bipolar affective disorders, and diabetes [60][61][62][63][64][65][66][67]. It has also been reported that the polymorphisms are related to clinical outcome in allogeneic stem cell transplantation and to fracture risk and the efficacy of hormone replacement therapy [28,68].…”
Section: Introductionmentioning
confidence: 99%